2021
DOI: 10.1002/tafs.10271
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Chinook Salmon Survival, Travel Time, and Floodplain Use Relative to Riverine Channels in the Sacramento–San Joaquin River Delta

Abstract: Floodplains provide multiple benefits to both resident and migratory fish species, including juvenile Chinook Salmon Oncorhynchus tshawytscha, but direct comparisons of survival during migration through a floodplain versus riverine routes are scarce. The Yolo Bypass is a broad floodplain of the Sacramento River that floods in about 30% of years in response to large, uncontrolled runoff events. We analyzed data from an acoustic telemetry study conducted in winter 2016 to estimate the proportion of tagged juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The DCC and its two radial gates were constructed by the U.S. Bureau of Reclamation in 1951 to divert freshwater from the Sacramento River into the interior Sacramento-San Joaquin River Delta (henceforth, "the Delta") to improve the water quality of diversions to the State Water Project and Central Valley Project export facilities (State Water Resources Control Board 1978). The opening of the DCC gates alters river and tidal flows in the Estuary and has been shown to incidentally entrain up to 80% of acoustically tagged emigrating juvenile Chinook Salmon into the interior Delta (Perry et al 2010(Perry et al , 2012(Perry et al , 2015(Perry et al , 2018Romine et al 2013;Steel et al 2013;Pope et al 2021). Although entrained individuals may still complete their out-migration, studies have indicated that these individuals may experience considerably higher mortality rates based on exposure to water exportation, high temperatures, increased predation risk, and pollution (Kjelson and Brandes 1989;Brandes and McLain 2001;Newman and Brandes 2010;Buchanan et al 2013).…”
Section: Impact Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCC and its two radial gates were constructed by the U.S. Bureau of Reclamation in 1951 to divert freshwater from the Sacramento River into the interior Sacramento-San Joaquin River Delta (henceforth, "the Delta") to improve the water quality of diversions to the State Water Project and Central Valley Project export facilities (State Water Resources Control Board 1978). The opening of the DCC gates alters river and tidal flows in the Estuary and has been shown to incidentally entrain up to 80% of acoustically tagged emigrating juvenile Chinook Salmon into the interior Delta (Perry et al 2010(Perry et al , 2012(Perry et al , 2015(Perry et al , 2018Romine et al 2013;Steel et al 2013;Pope et al 2021). Although entrained individuals may still complete their out-migration, studies have indicated that these individuals may experience considerably higher mortality rates based on exposure to water exportation, high temperatures, increased predation risk, and pollution (Kjelson and Brandes 1989;Brandes and McLain 2001;Newman and Brandes 2010;Buchanan et al 2013).…”
Section: Impact Statementmentioning
confidence: 99%
“…2013; Pope et al. 2021). Although entrained individuals may still complete their out‐migration, studies have indicated that these individuals may experience considerably higher mortality rates based on exposure to water exportation, high temperatures, increased predation risk, and pollution (Kjelson and Brandes 1989; Brandes and McLain 2001; Newman and Brandes 2010; Buchanan et al.…”
Section: Introductionmentioning
confidence: 99%
“…The Yolo Bypass is an engineered floodplain that is only accessible to downstream migrating fish when the Sacramento River stage exceeds the 10.2 m height of the 2.9 km long Fremont Weir. The Yolo Bypass floodplain contains valuable habitat for rearing (Katz et al 2017;Takata et al 2017) and actively migrating juvenile Chinook salmon (Johnston et al 2018;Pope et al 2021). Migrating fish that enter the Yolo Bypass avoid entrainment in the interior Delta and telemetered fish released directly into the Yolo Bypass have been demonstrated to have survival similar to those released directly into the Sacramento River (Johnston et al 2018;Pope et al 2021).…”
Section: Study Areamentioning
confidence: 99%
“…The Yolo Bypass floodplain contains valuable habitat for rearing (Katz et al 2017;Takata et al 2017) and actively migrating juvenile Chinook salmon (Johnston et al 2018;Pope et al 2021). Migrating fish that enter the Yolo Bypass avoid entrainment in the interior Delta and telemetered fish released directly into the Yolo Bypass have been demonstrated to have survival similar to those released directly into the Sacramento River (Johnston et al 2018;Pope et al 2021). During large flood events, the Yolo Bypass can carry up to four times more water than the mainstem Sacramento River (Suddeth Grimm and Lund 2016).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation